Penerapan Win-Win Solution dalam Sengketa Pengadaan Barang/Jasa Pemerintah Berdasarkan Kontrak Secara Elektronik Melalui Katalog Elektronik/E-Purchasing - Karwiyah; Farina Firda Eprilia; Adinda Putri Pertiwi (Jurnal Hukum Lex Generalis, 2022)
The form of implementation of the agreement/contract that occurs between government and private sectors is the procurement of goods/services as contained in Presidential decree No.18 of 2018 as amended by Presidential Decree No. 21 of 2021. The agreement was carried out with a conventional system that developed into an electronic system through an E-Purchasing application which can be implemented by direct purchase method, price negotiation, requests for quotation, and/or other methods. If there is a contract dispute, deliberation is the priority. If it is not successful, then the dispute resolution is carried out in the court which creates a win-win solution. So in this case, litigation is the last resort.